Private equity - Jenkinson, T (CESifo Group Munich, 2009)
The credit crunch was most likely viewed as a mixed blessing by many private equity executives. On the one hand, it signalled the end of the most favourable set of economic conditions the private equity industry had ever witnessed: abundant capital, low interest rates, increasing stock market values and a truly amazing willingness amongst banks and other investors to provide debt financing on a scale and on terms never previously observed. But the clouds that have descended since August 2007 have at least one silver lining: the intense public scrutiny of the private equity industry has been, to some extent, diverted into other areas of the financial system, in particular the investment banks, rating agencies, imploding hedge funds and structured vehicles etc. During this crisis, private equity funds have attracted little attention, except for their activities in taking advantage of banks’ desire to sell debt backing private equity deals. But the private equity industry remains active, having attracted large amounts of committed capital, and is continuing to invest – albeit not in the headline grabbing purchases of large public companies. And public scrutiny is redeveloping.